Curriculum Analysis of Persis 110 Bandung in the Curriculum Perspective Curriculum Reconstruction Social - Kahpiana Kahpiana; Rusman Rusman (Jurnal al-Thullab, 2020)
This study aims: 1) to provide a description of curriculum planning, 2) the implementation of the pesantren curriculum, 3) the evaluation of the pesantren curriculum, in the perspective of the social reconstruction curriculum. This research was conducted because the PPI curriculum number 110 has the characteristic of translating the implementation of learning consciously to form a critical person and be able to make students as pioneers in social sustainability in the pesantren environment and beyond. This research method is descriptive qualitative. The research design involved the triagulation method with interviews with the dipesantren steakholders, the madrasah head, deputy head of the curriculum, madrasa aliyah teachers, study of curriculum documentation, and observations of learning at the pesantren. The results of the study, curriculum planning in the pesantren in the perspective of social reconstruction have not included planning criteria in view of social reconstruction, curriculum implementation in the pesantren in the perspective of social reconstruction there is a revival between teachers and students / students in an equal communication process, evaluation of the curriculum in the pesantren in social reconstruction perspective, there is an integrated homework strategy pattern as part of a continuous and objective assessment pattern, evaluation aims to create a qualitative value that is honesty, the implications of this research for the process of treasuring the social reconstruction curriculum. Abstrak:  Tujuan umum penelitian ini adalah 1) untuk memberikan deskripsi tentang perencanaan kurikulum, 2) implementasi kuriukulm pesantren, 3) evaluasi kurikulum pesantren, dalam cara pandang kurikulum rekonstreuksi sosial. Penelitian ini dilakukan karena kurikulum PPI Nomor 110 memilki ciri khas menerjemahkan implementasi pembelajaran secara sadar membentuk pribadi yang kritis serta mampu menjadikan santri sebagi  pionir dalam keberlangsungan sosial di lingkungan pesantren dan diluar. Metode penelitian ini adalah deskriptif kualitatif. Desain penelitian melibatkan metode triagulasi dengan metode wawancara dengan stakeholder dipesantren tersebut, kepala madrasah, wakil kepala bagian kurikulum, guru madrasah aliyah, studi dokumentasi kurikulum, dan observasi pembelajaran di pesantren tersebut. Hasil penelitian, perencanaan kurikulum di pesantren tersebut dalam perspektif rekonstruksi sosial belum mencangkup kriteria perencanaan dalam pandangan rekonstruksi sosial, implementasi kurikulum di pesantren tersebut dalam perspektif rekonstruksi sosial adanya keterbangunan antara guru dan siswa / santri dalam proses komunikasi yang setara, evaluasi kurikulum di pesantren tersebut dalam perspektif rekonstruksi sosial, ada pola integrateg homework sebagai bagian dari pola penilaian secara terus menerus dan dilakukan secara objektif, evaluasi bertujuan untuk terciptannya nilai kualitatif yakni kejujuran, implikasi penelitian ini untuk proses khazanah tentang kurikulum rekonstruksi sosial.